The Christmas guest : a novella - Swanson, Peter, 1968- (William Morrow, an imprint of HarperCollinsPublishers, 2023)
When a last-minute invitation from fellow student Emma Chapman brings her to Starvewood Hall for the holidays, Ashley Smith, an American art student in London, discovers this seemingly charming English village's grim history when a local girl is brutally murdered and Emma's brother is linked to the crime.